ChemInform Abstract: M2+ and Ln3+‐Catalyzed Synthesis of a [1, 2, 4]Triazine Core via Intramolecular C—H/N—H Functionalization and C—N Bond Formation (M: Mn, Zn, Cd; Ln: Dy, Tb). Issue 25 (5th June 2015) - Chen, Wen‐Bin; Li, Zhi‐Xin; Yu, Xin‐Wei; Yang, Meng; Qiu, Yan‐Xuan; Dong, Wen
Abstract: A new approach to the direct construction of the 1, 2, 4‐triazine core starting from eight azo‐conjugated aromatic compounds via transition or lanthanide metal‐catalyzed cross‐dehydrogenative coupling reactions under hydrothermal conditions is reported.